2014
DOI: 10.4103/0971-3026.130701
|View full text |Cite
|
Sign up to set email alerts
|

Variations in superior thyroid artery: A selective angiographic study

Abstract: Aim:To investigate variations in superior thyroid artery (STA) based on digital subtraction angiography (DSA).Materials and Methods:Twenty five angiography studies of 15 pts performed between June 2010 and December 2012 were retrospectively evaluated. These patients underwent DSA of the head and neck region as a part of their superselective neoadjuvant intra-arterial chemotherapy protocol for treatment of laryngeal and hypopharyngeal cancers. Depending upon the location of the tumor, unilateral or bilateral ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 10 publications
3
18
0
2
Order By: Relevance
“…Absence of inferior and/or superior thyroid arteries with absence of thyroid tissue seems to be the most reliable tool for confirmation of the diagnosis. In the first case we noted an absence of inferior thyroid artery of the left side while in second case both the arteries were absent [11], [12]. CT scan however remains an expensive investigation with risk of radiation and contrast injection, when compared to high resolution sonography.…”
Section: Discussionmentioning
confidence: 73%
“…Absence of inferior and/or superior thyroid arteries with absence of thyroid tissue seems to be the most reliable tool for confirmation of the diagnosis. In the first case we noted an absence of inferior thyroid artery of the left side while in second case both the arteries were absent [11], [12]. CT scan however remains an expensive investigation with risk of radiation and contrast injection, when compared to high resolution sonography.…”
Section: Discussionmentioning
confidence: 73%
“…The STA is a consideration in many surgeries and accurate clinical anatomical knowledge of the STA is important to minimizing surgical complications. Most anatomical studies of the STA have been done by direct observation of its anatomy in the body, although there are a small number of angiographic studies [ 5 7 12 13 14 ]. These studies have mostly been concerned with identifying the pattern of origin of the STA or, occasionally, the thickness of its branches.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al [ 7 ] conducted an angiographic study of 25 STAs of cadavers and identified their pattern of origin. In their study, the STAs on the right side of the body arose from the ECA, CB, CCA, and in one case, from the internal carotid artery (ICA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations